2009
DOI: 10.1590/s0104-66322009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous titania in rutile phase with pore-stable structure

Abstract: -Metastable-to-stable transformation in oxides is always associated with drastic reduction in surface area and/or porosity. Therefore, all earlier efforts to stabilize the pore structure of oxides undergoing a metastable-to-stable phase transformation are interesting for both scientific and technological concerns. This work presents a new experimental technique for catalytic oxide production through sonication in acid solution for attainment of the anatase-rutile transformation. Mesoporous structure of titania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Hydrated titania-based catalysts have been used for a diversity of applications, such as support for catalysts, pigment, ceramics, paper industry, cosmetics, and staple fibers that are some of the wide variety of commercial applications. Thermal stability of mesoporous structures is a critical parameter for catalysis applications [17]. The mesoporous TiO 2 offers better performance as catalyst, due to easier accessibility of bigger molecules to the internal channels.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrated titania-based catalysts have been used for a diversity of applications, such as support for catalysts, pigment, ceramics, paper industry, cosmetics, and staple fibers that are some of the wide variety of commercial applications. Thermal stability of mesoporous structures is a critical parameter for catalysis applications [17]. The mesoporous TiO 2 offers better performance as catalyst, due to easier accessibility of bigger molecules to the internal channels.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of ionic layers which undergo excitation could be assisted by the presence of aliovalent impurities which give rise to oxygen vacancies but tend to retain layer integrity. This is evidenced in many reported studies (dos Santos et al 2009). This aspect has not been examined fully in the A → R transformation of nano-TiO 2 .…”
Section: Anatase-rutile Phase Transformationmentioning
confidence: 95%
“…In their extensive and insightful investigations of phase transition of TiO 2 , Lee Penn and Banfield (1998) observed that brookite is a polytype of anatase and its inter-conversion only involves the displacement of titanium atoms into adjacent octahedral sites. In somewhat related work on the preparation of mesoporus titania, Correa and co-workers (dos Santos et al 2009) have shown that creation of defects by sonication can bring about anatase-to-rutile transformation at lower temperatures. Banfield and Veblen (1992) have proposed a very attractive transformation mechanism based on a structural concept of 'fundamental building blocks'.…”
Section: Anatase-rutile Phase Transformationmentioning
confidence: 99%
“…Further increase in the concentration of dopant above the solubility limit it shows a decrease in both the strain and the lattice constant [27,28]. This may be due to the arrangement of Dy 3+ materials made were of non-stoichiometric with oxygen vacancy that indicates the enhanced photocatalytic activity [29]. This may be due to the incorporation of Dy 3+ , Eu 3+ and Tb 3+ ions which suppresses the growth of TiO 2 nanocrystals to a greater extent.…”
Section: Equipmentsmentioning
confidence: 99%
“…It is also observed that the positions are almost invariant and is around 25.22° for all RE doped TiO 2 . This indicates that the incorporation of the RE dopants is responsible for shifting in peak positions[29]. The amalgamation of RE in TiO 2 lattice results in deformation of the lattice arrangement by dislocating Ti 4+ ion due to mismatch in the ionic radii between RE and Ti 4+[30].…”
mentioning
confidence: 96%